Monitoring capabilities of 7-10-year-old children during the learning process at school - Samokish, Ivan (My University, 2019)
The studies give reason to believe that the definition of functional capabilities of children 7-10 years using reflexometer methods omegametrii fairly accurately reflect the physiological processes that occur in the brain in a state of muscular rest, during exercise and during the early recovery period. With a certain degree of reliability methods allow the judge reserves the compensatory and adaptive processes of the child's body and are key to the complex monitoring functionality in the learning process at school. Effect of exercise capacity in regulatory mechanisms of children 7-10 years organism was traced by changing the overall functional state of the brain parameters (OFS brain). Before functional testing corresponding figures were within the physiological norm. The reaction of the central nervous system to physical stress was different. Most children 7-10 years figures omega-potential (OP) of the brain in a state of relative muscular rest are in the normal range. Analysis of the individual reactions of the brain according to physical stress omegametrii allowed children divided into two groups according to the reaction type: increasing and decreasing OP. It was revealed that the increase in omegapotential was observed in subjects with low and decrease - with high OP values. It can be concluded that the physical load do not cause CNS overreaction and activate converged changes omega-potential which are caused by initial values of constant potential.
Samokish I. Monitoring capabilities of 7-10-year-old children during the learning process at school / I. Samokish // Journal of Physical Education and Sport (JPES). – 2019. - Vol. 19, Is. 4, Art 372. - P. 2453-2457.
Keywords: physical health; omegametriya; general functional state of the brain; functional testing; exercise